Adverse events in different administration routes of semaglutide: a pharmacovigilance study based on the FDA adverse event reporting system - Niu, Kaibin; Fan, Maoxia; Gao, Wulin; Chen, Chen; Dai, Guohua (Frontiers in Pharmacology, 2024)
Background: With the continuously increasing incidence of type 2 diabetes, glucagon-like peptide-1 (GLP-1) receptor agonists, known for their dual benefits of effectively controlling blood glucose levels while also reducing weight and lowering cardiovascular disease risks, have been widely employed in the treatment of this condition.In recent years, semaglutide has garnered significant attention as the only injectable and orally administered glucagon-like peptide-1 receptor agonist (GLP-1RA).The aim of this study is to compare the adverse event profiles of semaglutide across different routes of administration by analyzing the adverse event reporting system of the U.S. Food and Drug Administration (FDA). Methods: Data was extracted from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database, specifically focusing on the period from the fourth quarter of 2017 to the fourth quarter of 2023.A comparative analysis was conducted using disproportionality analysis, reporting odds ratio (ROR), and stratified analysis methods to assess and compare the signals of adverse events (AE) and the time to onset of adverse reactions associated with different routes of administration of semaglutide from 2017 to 2023. Results: A total of 22,287 adverse reaction records related to semaglutide were identified in the FAERS database.A comparative analysis was performed on 16,346 records of subcutaneous administration and 2,496 records of oral administration.Different routes of administration can lead to varying adverse reaction outcomes. Compared to oral administration, subcutaneous injection is more likely to result in adverse events related to the endocrine system. Additionally, it significantly accelerates the onset of adverse reactions.The comparative analysis of all relevant results indicates that semaglutide can lead to different adverse reaction events depending on the route of administration. Furthermore, there are significant differences in the time of onset for these adverse reactions. Conclusion: Semaglutide exhibits variations in adverse reaction events and the time of onset across different routes of administration.Therefore, when selecting the route of administration for semaglutide, clinicians should consider the risk of adverse events and weigh them against the clinical benefits. Based on these considerations, appropriate guidance and recommendations can be provided to patients.